2009
DOI: 10.1128/iai.00272-09
|View full text |Cite
|
Sign up to set email alerts
|

Mesenteric Lymph Nodes Confine Dendritic Cell-Mediated Dissemination ofSalmonella entericaSerovar Typhimurium and Limit Systemic Disease in Mice

Abstract: In humans with typhoid fever or in mouse strains susceptible to Salmonella enterica serovar Typhimurium (S. Typhimurium) infection, bacteria gain access to extraintestinal tissues, causing severe systemic disease. Here we show that in the gut-draining mesenteric lymph nodes (MLN), the majority of S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
108
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 102 publications
(114 citation statements)
references
References 38 publications
6
108
0
Order By: Relevance
“…Indeed, precedence for the importance of luminal spread and a pool of replicating pathogens in the intestinal mucosa has been established in models of L. monocytogenes, Salmonella enterica, and Yersinia pseudotuberculosis infection (47)(48)(49). Melton-Witt et al proposed that luminal shedding acts as a mechanism for bacterial spread and further dissemination after showing that L. monocytogenes shed from villi into the lumen can infect Peyer's patches (47).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, precedence for the importance of luminal spread and a pool of replicating pathogens in the intestinal mucosa has been established in models of L. monocytogenes, Salmonella enterica, and Yersinia pseudotuberculosis infection (47)(48)(49). Melton-Witt et al proposed that luminal shedding acts as a mechanism for bacterial spread and further dissemination after showing that L. monocytogenes shed from villi into the lumen can infect Peyer's patches (47).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the yopK mutant reached the MLN that constitute the critical barrier for preventing systemic infection by both commensals and pathogens (42,43) but failed to disseminate further. Analysis of initial colonization of the different intestinal organs using IVIS and immunofluorescence staining showed that Y. pseudotuberculosis lacking YopK colonized PPs and MLN more rapidly than the wild-type strain.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery was performed as previously described (40). Briefly, the small intestine and cecum, together with MLN, were exteriorized through a 1-cm-wide incision along the abdomen and kept humid with PBS.…”
Section: Methodsmentioning
confidence: 99%